Putting things in and taking them out of containers: a young child's interaction with objects - Nishio, Chihiro; Nozawa, Hikaru; Yamazaki, Hiroe; Kudo, Kazutoshi (Frontiers in Psychology, 2023)
Introduction How does the behavior of putting things away (putting them in) in a container and using them again (taking them out) develop in young children? Though object interaction is one of the most examined topics in child development, research on organized behavior with various objects and containers at home is lacking. Rather than conducting experiments on young children's interactions with objects, this study focused on natural child–object interaction in the home. Methods We conducted a case study on a young child's natural interaction with objects at home, focusing on when the child puts them in or takes them out of a container (the shelf, the cabinet, or the box). The study took place over 2½ years. Results The behaviors of putting many objects in a container and taking them out appeared at 9 months old. After acquiring the skill of walking, the child carried the objects using bags. Putting objects in and taking them out was embedded in the locomotion, and the child prepared the containers of toys before play. Pulling as many objects out as possible became rare after 19 months of age. Taking objects out became more appropriate in that context. The child brought out the container before the activity and put things away afterward. Discussion Based on these findings, the development of organized object interaction as well as the anticipation and significance of the naturalistic longitudinal observations are discussed.